A FEMINIST INTERPRETATION OF QUR’ANIC TEXTS BY AMINA WADUD AND ZAITUNAH SUBHAN - Noor, Muhammad Fauzi (Prodi Pendidikan Agama Islam STAI Darul Falah, 2024)
Islam Rahmatan Lil Alamin is a genuine expression that underscores Islam's transformative impact on societal systems during its emergence, particularly in addressing gender discrimination. Wadud and Subhan contribute significantly to contemporary Quranic exegesis by providing frameworks that align with Islam's foundational ethos of justice and equality, addressing modern gender issues through scholarly reinterpretation of sacred texts. Their works highlight the dynamic interplay between historical context and contemporary application, fostering a deeper understanding of Islam's teachings on gender relations. The methodology of this research comprises a qualitative approach that integrates textual analysis of the Quran with critical discourse analysis of classical and contemporary interpretations. The primary sources include the Quran and Hadith, focusing on Surah Al-Hujurat verse 13 and other relevant verses. Secondary sources include classical tafsir (exegesis) by scholars such as Ibn Kathir and contemporary works by feminist scholars like Amina Wadud and Zaitunah Subhan. This study aims to rediscover the essence of Islamic teachings that liberate humanity from all forms of injustice and discrimination, while also offering constructive criticism of interpretations that do not align with Islam's primary objectives. This research introduces a comprehensive and multidisciplinary approach, highlighting the importance of revising classical interpretations to support gender equality in accordance with Islamic principles.